MODEL KEPRIBADIAN ISLAMMELALUI PENDEKATAN PSIKOSUFISTIK - Abdul Mujib (Universitas Islam Negeri Fatmawati Sukarno, 2015)
Through psycho-Sufi approach that emphasizes the taste (dzawqiyah) and purification processes (tazkiyah al-nafs), the Islamic personality leads to the formation of the human mind. Model of Personality in psychosufistic is more focused on self-cleaning (tazkiyah al-nafs) of sin, so that more clean from sin and evil person the better the personality. Certainly does not stop there, but until the filling themselves with good conduct and felt themselves to be spiritual majesty and love of God